hi!

ok, i know that deriv(cscx) = -cscxcotx
and that
deriv(cos) = -sinx
deriv(cotx) = -((cscx)^2)

my question is:
is this (statements below) correct?

antideriv(cscxcotx) = -(cscx)

antideriv(sinx) = -cosx

antideriv((cscx)^2)= -cotx

were those antiderivatives above correct?

1 answer

yes.
Similar Questions
  1. helloi know that deriv(cscx) = -cscxcotx and that deriv(cos) = -sinx deriv(cotx) = -((cscx)^2) my question is: is this
    1. answers icon 1 answer
  2. My previous question:Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) =
    1. answers icon 2 answers
  3. express in sinx1 1 ---------- + -------- cscx + cotx cscx - cotx and express in cosx 1 + cot x ------- - sin^2x cscx = 1/sinx so
    1. answers icon 0 answers
  4. express this in sinx(1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is that right?? and B) express in cosx problem: is 1 +
    1. answers icon 1 answer
more similar questions